GAMBARAN INEFESIENSI PENAGIHAN CT SCAN SIMULATOR SEBAGAI INISIASI AWAL AUDIT ADMINISTRASI KLAIM (AAK) BPJS KESEHATAN PADA RS VINA ESTETIKA: GAMBARAN INEFESIENSI PENAGIHAN CT SCAN SIMULATOR SEBAGAI INISIASI AWAL AUDIT ADMINISTRASI KLAIM (AAK) BPJS KESEHATAN PADA RS VINA ESTETIKA - Yusti, Rahayu (Jurnal Jaminan Kesehatan Nasional, 2024)
A CT Scan Simulator is a tool used to determine the size, shape, and location of a tumor to help the radiotherapy team determine the next treatment plan. Vina Estetica General Hospital is a public hospital that provides CT Scan Simulator services based on the permission of Perka BAPETEN as radiotherapy management and follow-up in malignancy cases. This study uses a descriptive method through a quantitative approach, aiming to describe the inefficiency of CT-Scan Simulator billing used as a support for diagnosis enforcement based on the Indonesian-Case Based Groups (INA CBGs) tariff costs. The technique used was purposive sampling with inclusion and exclusion criteria. Secondary data collection was carried out retrospectively in the form of claim files for the period January 2020 - November 2023 as many as 308 samples were taken randomly. The results showed that there were 283 (83%) CT Scan Simulator billing claims aimed at supporting diagnosis enforcement and resulting in billing inefficiencies in the INA CBGs claim rates being higher